2013
DOI: 10.1080/09540121.2013.808733
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in HIV-related stigma in Kenya

Abstract: Stigma associated with HIV/AIDS directly and indirectly drives HIV transmission. We examined how factors associated with HIV-related stigma differed by gender, using data from the 2008-2009 Kenya Demographic and Health Survey (KDHS). Descriptive, bivariate and multinomial logistic regression analyses were conducted on selected HIV-related stigma indicators for men and women. Bivariate analyses showed significant gender differences in the overall HIV Stigma index with a higher proportion of women than men prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 25 publications
0
32
0
Order By: Relevance
“…Male sex was a risk factor for both having HIV infection and for the occurrence of AIDSassociated OIs (male-to-female ratio was 5:1). This was not the case in other parts of the world, such as sub-Saharan areas of Africa [14]. This may be due to the increased incidence among males of unsafe sex and drug abuse compared to females in Bahrain and the late seeking of medical advice in male patients.…”
Section: Discussionmentioning
confidence: 77%
“…Male sex was a risk factor for both having HIV infection and for the occurrence of AIDSassociated OIs (male-to-female ratio was 5:1). This was not the case in other parts of the world, such as sub-Saharan areas of Africa [14]. This may be due to the increased incidence among males of unsafe sex and drug abuse compared to females in Bahrain and the late seeking of medical advice in male patients.…”
Section: Discussionmentioning
confidence: 77%
“…Part of the reasons for this could be due to: (i) HIV related stigma which is known to be higher in females than in males, and prohibits them out from HIV care seeking [58, 59]; (ii) Lower literacy status in females than males, which is a big challenge that prevent women from optimising the benefit of HIV care [60], (iii) higher usage in females than males of traditional healers which hinders females from taking ART consistently [61], and (v) lack integration between modern and traditional medicines which has been identified as one of the key factors in for a consistent uptake of ART programs in Ethiopia [62]. Similar to findings by Meloni and colleagues[63], discontinuation was higher among patients with immunological failure than their comparator.…”
Section: Discussionmentioning
confidence: 99%
“…We also found that HIV-related stigma in the general population appeared to be more prevalent among women than among men, perhaps reflecting gender differences in HIV-related knowledge, formal education, socioeconomic standing, and personal experiences with PLHIV. 59 Thus, it remains evident that additional interventions to reduce HIV-related stigma—such as educational campaigns, 31 changes to laws or policies that institutionalize stigma, 14 and livelihood interventions 24 —will be needed and that such interventions may need to be tailored to reflect gender differences.…”
Section: Discussionmentioning
confidence: 99%